Competent Electrocatalytic and Photocatalytic Proton Reduction by a Dechelated [Co(tpy)2]2+ Scaffold. Issue 28 (31st July 2017) - Ahmad, Ejaz; Majee, Karunamay; Patel, Jully; Das, Babulal; Padhi, Sumanta Kumar
Abstract : The complexes [Co II (QCl‐tpy)2 ]Cl2 (1 ) and [Co III (QCl‐tpy)2 ](PF6 )3 [where QCl‐tpy = 2‐chloro‐3‐(2, 6‐di(pyridin‐2‐yl)pyridine‐4‐yl) quinoline] have been synthesised and characterised by various spectroscopic techniques. Complex1 acts as a hydrogen‐evolving catalyst under electrochemical and photochemical conditions. It exhibits photochemical proton reduction by irradiation with visible light in the presence of [Ru(bpy)3 ]Cl2 as a photosensitiser and ascorbic acid as a sacrificial electron donor. The formation of [Co II (QCl‐tpy)( 2 QCl‐tpyH)DMF] 3+ was detected after 24 h, due to the dechelation of one of the QCl‐tpy ligands in DMF/H2 O (95:5 v/v, where 2 QCl‐tpy is a bidentate ligand). The introduction of 2‐chloroquinoline into the terpyridine framework reduces the overpotential by 300 mV for proton reduction, as compared with the parent [Co(tpy)2 ] 2+ complex. Considering the spectroscopic studies, the possible involvement of the active species are depicted and mechanistic paths are proposed. Abstract : The complexes [Co II (QCl‐tpy)2 ]Cl2 and [Co III (QCl‐tpy)2 ](PF6 )3 [QCl‐tpy = 2‐chloro‐3‐(2, 6‐di(pyridin‐2‐yl)pyridine‐4‐yl) quinoline] have been synthesised and spectroscopically and electrochemically characterised. The catalytic hydrogen evolution and the stability of the active species have been analysed. The dechelation of one of the QCl‐tpy ligands plays a crucial role in catalysis.